Corrosive Effect of Nifedipine in the Upper Gastrointestinal Tract. Issue 1 (1999) - Lavy, Alexandra
Abstract : Upper gastrointestinal tract mucosa is prone to injury. Drugs may disturb gastric mucosa protective mechanisms and cause damage. Injury by NSAIDs is a well described complication. Nifedipine, a widely used drug, was not described before as having a potential to damage gastrointestinal mucosa. We describe here, two patients, who developed esophageal and gastric mucosal damage, probably related to Nifedipine ingestion.